The Demand for Wheat under Non-Linear Pricing in Pakistan - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 1987)
It is common for economic agents to face non-linear pricing schedules. This poses difficulties for the estimation of demand functions but also advantages in that we have price variation in a cross-section. We illustrate this with two examples from Pakistan: the urban rationing of wheat and the demand for wheat by rural households that produce and consume wheat. In the first case consumers have to pay higher prices for purchases above the ration, and in the second buying and selling prices differ. Demand elasticities are estimated using maximum likelihood methods. These estimates are considerably different from those obtained using standard LES assumptions.